POSSIBLE COMPLICATIONS RESULTING FROM THIRD MOLAR EXTRACTION: LITERATURE REVIEW - Eugênio, Raysna; Menezes, Dâmaris; Paulo Melo Lócio, João (Health and Society, 2023)
Third molar extraction surgery presents a considerable potential risk of triggering complications. In view of this, it is imperative that there is careful planning, aiming to prevent accidents during the procedure and minimize possible complications in the intra- and postoperative period. Intraoperative complications may include hemorrhage, fracture of the maxillary tuberosity and oroantral communication, and postoperative complications may include alveolitis, edema, and paresthesia of the inferior alveolar nerve. 17 studies indexed in the BVS, LILACS, Scielo and Pubmed databases were selected. The selection of articles occurred in accordance with the inclusion and exclusion criteria. Therefore, the importance of having in-depth knowledge and solid skills on the subject is highlighted, both for a preventive approach and for dealing eﬀectively with the situation in question.